Basic properties and potential uses of saling-saling wood - Mody Lempang (Jurnal Penelitian Kehutanan Wallacea, 2016)
This research was carried out to examine the basic properties (anatomical structure, chemical, physical and mechanical) of saling-saling wood (Artocarpus teysmanii Miq.) taken from natural forest in Luwu Timur District, South Sulawesi Province. The Potential uses of this wood was determined by considering those properties and wood uses currently employed by the local inhabitants. Results revealed that saling-saling had clearly distinct heartwood and sapwood, sapwood yellowish white and heartwood yellowish brown in colour, figure on tangential sections sometimes show discontinuous dark coloured ribbons, fine or uneven texture, straight grain and sometimes rather interlocked, glossy wood surface , rough surface, and moderate in hardness, the fiber is remarkably long with very thin wall thickness, and this fiber quality is classified in class II for manufacturing paper pulp. The chemical content is composed of high cellulose, low pentose, moderate lignin, high extractive, moderate ash and high silicate. Saling-saling is a light wood with a specific gravity of 0.40, very low in shrinkage and classified as a class III wood strength. Potential uses are for light construction material, canoe/boat, cheap furniture, handicraft, veneer for plywood, laminated lumber, boxes, concrete forms, particle board, fiber board and paper pulp.